PERAN REMAJA MASJID DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER PADA ANAK USIA DINI DI TPQ MADINAH MASJID AGUNG JAMI’ KOTA MALANG - Muhammad Ro’uf; Rosichin Mansur; Achmad Faisol (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to describe the character of early childhood in the TPQ Medina of the Great Mosque of Jami 'Malang, and to describe the role of mosques in planting the values of character education for children in the TPQ Medina of Great Mosque of Jami' Malang, and to describe the supporting factors and obstacles of adolescent mosques in planting the values of character education in early childhood at TPQ Madinah Jami Great Mosque 'Malang. The approach used is a qualitative approach, while the research is a case study. Data collection techniques used are observation, interview, documentation, while data analysis techniques use data reduction, data presentation, verification. This study aims to describe the character of early childhood in the TPQ Medina of the Great Mosque of Jami 'Malang, and to describe the role of mosques in planting the values of character education for children in the TPQ Medina of Great Mosque of Jami' Malang, and to describe the supporting factors and obstacles of adolescent mosques in planting the values of character education in early childhood at TPQ Madinah Jami Great Mosque 'Malang. The approach used is a qualitative approach, while the research is a case study. Data collection techniques used are observation, interview, documentation, while data analysis techniques use data reduction, data presentation, verification. The results of this study that adolescents of Malang Grand Mosque of Jami Great Mosque have a very important role in instilling the values of character education in early childhood. Teenagers of mosques have given many religious activities to early childhood children to be able to divert their views or attract the hearts of children, so that children can eliminate bad culture or customs that are in their environment. So that by providing a variety of positive activities that are owned by adolescent mosques in guiding children to be able to instill the values of character education in early childhood in a gradual and sustainable manner every day